The Effect Of Competence And Work Environment On Performance Employees With The Implementation Of Corruption-Free Areas As An Intervening Variable At The Class Ii Immigration Office Tpi Pematang Siantar - Sofyan Ansori Tondang; Kiki Farida Ferine; Darmilisani (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of competence and work environment on employee performance with the implementation of Corruption-Free Areas (WBK) as an intervening variable at the Class II Immigration Office of TPI Pematangsiantar. This study uses a quantitative approach with the Partial Least Square (PLS) method to test the relationship between latent variables. Data was obtained through the distribution of questionnaires to employees who were respondents in this study. The results of the study show that competence has a positive and significant effect on employee performance and on the implementation of Corruption-Free Areas. The work environment does not have a direct effect on employee performance, but it has a significant effect on the Corruption-Free Area. Furthermore, the Corruption-Free Zone has been proven to have a positive and significant effect on employee performance. The results of the indirect influence test showed that competence and work environment had an effect on performance through the Corruption-Free Zone as a mediation variable. Theoretically, this research strengthens the concept that improving competencies and establishing a conducive work environment can encourage the implementation of clean and corruption-free organizational governance, which ultimately has a positive impact on employee performance. Practically, the results of this research are expected to be a reference for government agencies in improving the quality of human resources and strengthening a work culture with integrity in order to realize a professional and accountable bureaucracy